2022
DOI: 10.1371/journal.pone.0272800
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of environmental impact labels on the sustainability of food purchases: Two randomised controlled trials in an experimental online supermarket

Abstract: Providing consumers with product-specific environmental impact information for food products (ecolabels) may promote more sustainable purchasing, needed to meet global environmental targets. Two UK studies investigated the effectiveness of different ecolabels using an experimental online supermarket platform. Study 1 (N = 1051 participants) compared three labels against control (no label), while Study 2 (N = 4979) tested four designs against control. Study 1 found significant reductions in the environmental im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…The design of the certificate or eco-label is key for it to produce the expected effects, both for consumers and for the whole system. Simple and clear graphic designs are more effective in influencing the risk perception and consumer behavior changes than any information table with text or numbers ( 72 , 73 ). However, a recent systematic review and meta-analysis concluded that despite different eco-label formats, all lead to selection and purchase of more sustainable products ( 74 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The design of the certificate or eco-label is key for it to produce the expected effects, both for consumers and for the whole system. Simple and clear graphic designs are more effective in influencing the risk perception and consumer behavior changes than any information table with text or numbers ( 72 , 73 ). However, a recent systematic review and meta-analysis concluded that despite different eco-label formats, all lead to selection and purchase of more sustainable products ( 74 ).…”
Section: Resultsmentioning
confidence: 99%
“…As there is an ecosystem of labels on foods, it is a common suggestion having different categories of labels together, for example, nutritional and environmental. But this suggestion has discrepancy on its impacts over the consumer ( 26 , 72 ), as it induces trade-offs between both ( 73 ). In addition, consumers have been found to limit cognitive ability, and to be distracted or dissuaded from considering many labels ( 41 ), and thus losing effect of the label ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulated store studies identi ed some promising interventions, including healthy swaps, which were effective in two RCTs included in the review (Koutoukidis et al, 2019;Payne Riches et al, 2019). Further studies in simulated online environments have examined interventions to promote sustainability including through information interventions such as carbon footprint or eco-labelling, with mixed results (Kanay et al, 2021;Panzone et al, 2021;Potter et al, 2022). It is unclear whether any effects detected in these virtual supermarket studies would transfer to real shopping conditions.…”
Section: Our Current Understanding Of Effective Interventions To Chan...mentioning
confidence: 99%
“…The findings about consumer food‐purchasing behaviours in WP2 will then be applied to inform the development and examine the impacts of in‐store interventions (designed in WP3). WP2 will examine the impact of potential shifts in consumer purchasing patterns (e.g., reducing meat purchasing or food swaps using data modelling of different scenarios), as well as of real‐world interventions, such as healthy start voucher top‐up coupons (Thomas et al, 2022), 60p value on selected fruit and vegetables (IGD, 2022), sustainability labelling (Potter et al, 2022). This WP will focus on how interventions could theoretically influence purchasing of healthier and environmentally sustainable foods, both independently and combined.…”
Section: Fio Food Work Packagesmentioning
confidence: 99%